Interactive effects of intercropping and mulching under conservation tillage as sustainable agriculture increased cotton productivity - Adil, Muhammad; Zhang, Cheng; Yao, Zijie; Lu, Siqi; Qin, Ziyuan; Wang, Jingcao; Mahmood, Arshad; Riaz, Muhammad Waheed; Lu, Heli (Frontiers in Ecology and Evolution, 2023)
Climate change is a great threat to food security. Recent floods in Pakistan could be taken as an example. In current climate change scenario, there is a dire need to develop methods that increase crop productivity and lessen the threats of food insecurity in the areas having low crop production. A detailed field experiment was conducted to check the effects of intercropping and straw mulching under conventional tillage (CT) and no tillage (NT) systems on soil health indicators and cotton productivity at the experimental area of Khwaja Fareed University of Engineering and Information Technology (KFUEIT), Rahim yar khan, Pakistan. The main plot treatments comprised of CT and NT. The sub plot treatments were sole cotton (C1), cotton + mung-bean intercropping (C2), cotton + mung-bean + straw mulching (C3), and cotton + straw mulching (C4) under CT, while sole cotton (N1), cotton + mung-bean intercropping (N2), cotton + mung-bean + straw mulching (N3), and cotton + straw mulching (N4) under NT. Overall NT increased plant height by 18.4 %, chlorophyll a and b contents by 28.2% and 21.1%, mean boll weight by 17.9% and seed yield by 20.9% compared to CT (P< 0.05). Interaction of tillage and mulching maximized plant height by 7.0% under CT, and 21.8% under NT as compared to no mulching. Similarly, straw mulching under NT increased chlorophyll a and b contents by 41.9% and 28.5%, mean boll weight by 26.9% and cotton seed yield by 23.0% as compared to no mulching under NT. Intercropping decreased crop yield without straw mulching but increased it under straw mulching. Also, straw mulching increased soil physico-chemical properties under NT that contributed to increase the crop productivity. We conclude that straw mulching under NT might be a promising practice for enhancing the cotton yield and productivity and soil health in low productivity areas.